La construcción del capitalismo global : la economía política del imperio estadounidense - Panitch, Leo; Gindin, Sam; Amoroto Salido, José María; Panitch, Leo. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2015)
The all-encompassing embrace of world capitalism at the beginning of the twenty-first century was generally attributed to the superiority of competitive markets. Globalization had appeared to be the natural outcome of this unstoppable process. But today, with global markets roiling and increasingly reliant on state intervention to stay afloat, it has become clear that markets and states aren't straightforwardly opposing forces. In this groundbreaking work, Leo Panitch and Sam Gindin demonstrate the intimate relationship between modern capitalism and the American state, including its role as an "informal empire" promoting free trade and capital movements. Through a powerful historical survey, they show how the US has superintended the restructuring of other states in favor of competitive markets and coordinated the management of increasingly frequent financial crises.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed May 13, 2016)
Keywords: Capitalism -- United States; Finance -- United States; United States -- Foreign economic relations; United States -- Foreign relations; International finance; Globalization -- Economic aspects; Electronic books